2017
DOI: 10.1021/acs.jpclett.7b01740
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Methylammonium Dipoles in MAPbX3 (X = Br and I)

Abstract: Dielectric constants of MAPbX3 (X = Br, I) in the 1 kHz–1 MHz range show strong temperature dependence near room temperature, in contrast to the nearly temperature-independent dielectric constant of CsPbBr3. This strong temperature dependence for MAPbX3 in the tetragonal phase is attributed to the MA+ dipoles rotating freely within the probing time scale. This interpretation is supported by ab initio molecular dynamics simulations on MAPbI3 that establish these dipoles as randomly oriented with a rotational re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
138
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(162 citation statements)
references
References 64 publications
23
138
1
Order By: Relevance
“…110 The measurement of similar responses for both MAPbI 3 and CsPbI 3 by Ref. [119] supports this claim. Pb 2+ is highly polarisable due to its lone pair (6s 2 ) electrons, and is therefore expected to dominate the ionic dielectric response.…”
Section: B Dielectric Polarization In Practicementioning
confidence: 73%
See 2 more Smart Citations
“…110 The measurement of similar responses for both MAPbI 3 and CsPbI 3 by Ref. [119] supports this claim. Pb 2+ is highly polarisable due to its lone pair (6s 2 ) electrons, and is therefore expected to dominate the ionic dielectric response.…”
Section: B Dielectric Polarization In Practicementioning
confidence: 73%
“…Govinda et al argue that the 1/T dependency of the dielectric response, observed above 160K in Figure 2(a), implies rotational disorder in the ab plane. 119,120 The established dynamic disorder of molecular orientation and inorganic octahedral titling evidences the absence of true ferroelectricity in MAPbI 3 .…”
Section: Ferroic Properties Of Halide Perovskitesmentioning
confidence: 96%
See 1 more Smart Citation
“…8 of SI and Refs. 3,22,23), leaves no doubt that the transition at this temperature involves only octahedral tilting. The steplike stiffening, instead of softening, below T OT is a less conventional behavior.…”
mentioning
confidence: 98%
“…Changing the halogen species from chlorine to iodine drastically shifts the light emitted from the resulting LHPs from near‐ultraviolet to near‐infrared (Figure d) . Exploiting alloyed halide species at various ratios to occupy site‐X allows the flexible tuning of the bandgap of the resulting LHPs, resulting in continuously adjustable emissive spectra across the entire visible range (Figure d) . By comparison, the A‐cation plays a minor role in determining the energy level configuration of LHPs.…”
Section: Fundamental Properties Of Lhp‐ncsmentioning
confidence: 99%